I found the answer. hehehehehehehehrheehrhrh
Answer:
x^(5/6) + 4(x^(7/3))
Step-by-step explanation:
Simplify x to the 1/3 power MULTIPLIED BY (x to the 1/2 power + 2x to the 2 power )
Simplify x^(1/3) × (x^(1/2) + (2x)^2)
= x^(1/3)(x^(1/2)) + x^(1/3)((2x)^2)
= x^(1/3+1/2) + 4(x^(1/3+2))
= x^(5/6) + 4(x^(7/3))
x^(1/3) is y such that y^3 = x
(x^(1/3) × x^(1/3) × x^(1/3)) = x^(1/3+1/3+1/3) = x^1 = x
x^(1/2) = √2 = y such that y^2 = x
(2x)^2 = 4x^2
Answer:
x = ±6
Step-by-step explanation:
x^2/4=9
Multiply by 4 on each side
x^2/4 *4=9*4
x^2 = 36
Take the square root of each side
sqrt(x^2) = ±sqrt(36)
x = ±6
Answer:
I think its 28 feet
Step-by-step explanation:
2x2=4
3x8=24
24+4=28 ft
Answer:
2nd point
Step-by-step explanation: